Symptom Control in Patients With Recurrent Ovarian Cancer: Measuring the Benefit of Palliative Chemotherapy in Women With Platinum Refractory/Resistant Ovarian Cancer. (1st November 2009) - Friedlander, Michael; Butow, Phyllis; Stockler, Martin; Gainford, Corona; Martyn, Julie; Oza, Amit; Donovan, Heidi S.; Miller, Brigitte; King, Madeline
Abstract : Most women with advanced ovarian cancer will relapse and subsequently develop platinum-resistant/refractory ovarian cancer. The benefit of treatment is currently based on objective response rates, which are a crude measure of benefit. It would be clinically meaningful if we were better able to measure the benefit of palliative therapy and, in particular, ascertain whether cancer-related symptoms improve with treatment and how this impacts on quality of life. This paper reviews the management of patients with platinum-resistant/refractory ovarian cancer and highlights the gaps in our knowledge and shortcomings with the current approaches to measure the benefit of treatment. The ultimate objective is to describe and encourage recruitment to the Gynecologic Cancer Intergroup study that has recently opened. This study will recruit a large number of patients from around the world in an effort to develop more robust instruments to measure the benefit of chemotherapy and to understand the impact of chemotherapy on symptom control and quality of life. In addition, this study will give us an insight into how all patients are managed rather than a select minority who are treated in clinical trials.